Partos con circulares de cordón umbilical y su influencia en el apgar del recién nacido en el Hospital de Apoyo Integrado – II – IPSS Tarapoto - 1991 - Gálvez Díaz, Haydee Raquel (1992)
The study of 315 consecutive births of children who produced 72 viable births Circular Cord is presented. The Circular Cord was present in 22.9% of all births, the most common d1eposic16n around the fetal neck was 97.2%, of which the Single and Double Circular was 84.7 and 12.6 percent respectively correspond to the remaining Circulars Corps (2.8%). The average length Cord was 51 cms., And average lengths Single and Double Circular loe was 53 and 63 cms., respectively. Being the minimum lengths for Simple Circular 28 cms., And for Double, 63 cms. The lower one minute is High in the group round with a frequency of presentation of 90.3 percent and the Circular No similar results are recorded, but when analyzed in relation to the type and length Circular Cord analyzes the Circular Simple to Neck Short Length mode is determined Apgar Low (score 4-6). Also recorded birth weights between 2500 - 3999 grs. 87.5 percent in the corresponding almost the same percentage of newborns to Gestational Age Term.